Dispersion performance of nanoparticles in water - Li-sha MA; Zhan-tao HAN; Yan-yan WANG (Journal of Groundwater Science and Engineering, 2021)
Engineering Nanoparticles (ENPs)' superior characteristics of adsorption depends on their dispersion in the medium. In this study, multi-walled carbon nanotubes (nonmetal), iron nanoparticles and silver nanoparticles (metallic simple substance), and Nano-TiO2, Nano-Fe2O3 and Nano-ZnO (metal oxide) were selected and respectively added into pure water and aqueous solution with 1% Sodium dodecyl benzene sulfonate (SDBS) surfactant. The dispersion effects were compared by leaving the solutions standing at room temperature under ultrasound. The results show that the dispersion of iron nanoparticles is the lowestamong the six ENPs, and that of multi-walled carbon nanotubes (MWCTS) is the highest. Adding anionic surfactants (SDBS) can obviously improve the dispersion performance of ENPs. The concentration of solution decreases by only 5% in 10 daysafter adding 1% SDBS for ultrasonic dispersion.